Indigenous Wholistic Theory: A Knowledge Set for Practice - Absolon, Kathy (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
In this article, the author, establishes a knowledge set for Indigenous social work practice based on Indigenous wholistic theory. An overall framework using the circle is proposed and introduced followed by a more detailed and elaborated illustration using the four directions. The article identifies the need to articulate Indigenous wholistic theory and does so by employing a wholistic framework of the four directional circle. It then systematically moves around each direction, beginning in the east where a discussion of Spirit and Vision occurs. In the south a discussion of relationships, community and heart emerge. The western direction brings forth a discussion of the spirit of the ancestors and importance of Indigenous knowledge and Indigenous knowledge production. The northern direction articulates ideas surrounding healing and movements and actions that guide practice. Finally, the article begins with a discussion on all four directions together with a final examination of the center fire where all elements interconnect and intersect. Lastly, the article proclaims the existence of Indigenous wholistic theory as a necessary knowledge set for practice.